Assessment Of The General Medication Adherence Scale And Relation To Medication Belief Among Geriatric Patients Attending A Primary Healthcare Centre In The State Of Negeri Sembilan, Malaysia - Pk Choudhury, Payal Choudhury (2023)
The study aims to assess the General Medication Adherence Scale (GMAS) and its relation to medication belief among geriatric patients undergoing treatment in a primary health clinic setting.